Diseño de un sistema de información de costos para la producción de ganado bovino razas doble propósito, en la finca la teodorita / Macaravita Santander. (2023)
Livestock activity occupies great importance in the development of the Colombian economy, since its main challenge is aimed at the possibility of expanding, which is why it must be prepared to meet all the quality requirements of the market. However, productivity does not reach world standards, mainly due to the sector's lack of business vision, a situation reflected in the empiricism that is managed in the production units that comprise it, especially those in charge of small and medium-sized producers who have seen the production of his farm as the way to obtain his family income (CARMONA CARMONA & GONZÁLES PULGARÍN, 2010). Therefore, this research is based on the design of an adequate cost system for the La Teodorita cattle farm, in order to identify, classify and record the elements that make up the cost for each of the processes and which provides adequate information. for decision-making and serve as a reference for other production units.